Integrasi Agama Dan Sains Di PTKIN : UIN Sunan Kalijaga Yogyakarta - Muhammad Tis Atus Sobirin; Abdus Salam; Asnawan (4, 2026)
The integration of religion and science is a strategic agenda in the development of State Islamic Religious Higher Education Institutions (PTKIN) as a response to the scientific dichotomy that separates Islamic and modern sciences. This article aims to examine the concept, implementation, and significance of the integration of religion and science at UIN Sunan Kalijaga Yogyakarta, one of the pioneering PTKINs in developing an integrative scientific paradigm. This research uses a qualitative approach with a case study. Data were obtained through in-depth interviews, observations, and documentation studies, then analyzed using the Miles and Huberman interactive data analysis model. The results indicate that UIN Sunan Kalijaga has developed an integration-interconnection paradigm that places religion and science in a dialogical and complementary relationship. Religion is positioned as a source of values, ethics, and moral orientation, while science plays a role as a rational-empirical instrument in understanding and responding to social realities and global challenges. The implementation of the integration of religion and science is reflected in curriculum design, the development of multidisciplinary study programs, interdisciplinary research, and an open and critical academic culture. Despite facing several challenges, such as differing scientific paradigms and a tendency toward formalization, the integration model developed by UIN Sunan Kalijaga demonstrates significant potential for building inclusive, critical, and transformative Islamic scholarship. The integration of religion and science at UIN Sunan Kalijaga not only strengthens the Islamic identity of PTKIN but also enhances its contribution to global scientific discourse and the pursuit of Islamic higher education that is relevant to the demands of the times and oriented toward the welfare of civilization. Abstrak Integrasi agama dan sains merupakan agenda strategis dalam pengembangan Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) sebagai respons atas dikotomi keilmuan yang memisahkan ilmu-ilmu keislaman dan ilmu-ilmu modern. Artikel ini bertujuan untuk mengkaji konsep, implementasi, serta signifikansi integrasi agama dan sains di UIN Sunan Kalijaga Yogyakarta sebagai salah satu PTKIN pelopor dalam pengembangan paradigma keilmuan integratif. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Data diperoleh melalui wawancara mendalam, observasi, dan studi dokumentasi, kemudian dianalisis menggunakan model analisis data interaktif Miles dan Huberman. Hasil kajian menunjukkan bahwa UIN Sunan Kalijaga mengembangkan paradigma integrasi-interkoneksi yang menempatkan agama dan sains dalam relasi dialogis dan saling melengkapi. Agama diposisikan sebagai sumber nilai, etika, dan orientasi moral, sementara sains berperan sebagai instrumen rasional-empiris dalam memahami dan merespons realitas sosial serta tantangan global. Implementasi integrasi agama dan sains tercermin dalam desain kurikulum, pengembangan program studi multidisipliner, riset interdisipliner, serta budaya akademik yang terbuka dan kritis. Meskipun menghadapi sejumlah tantangan, seperti perbedaan paradigma keilmuan dan kecenderungan formalisasi integrasi, model integrasi yang dikembangkan UIN Sunan Kalijaga menunjukkan potensi besar dalam membangun keilmuan Islam yang inklusif, kritis, dan transformatif. Integrasi agama dan sains di UIN Sunan Kalijaga tidak hanya memperkuat identitas keislaman PTKIN, tetapi juga meningkatkan kontribusinya dalam percakapan keilmuan global serta upaya menghadirkan pendidikan tinggi Islam yang relevan dengan tuntutan zaman dan berorientasi pada kemaslahatan peradaban.